Employee perception regarding turnover decision-in context of Bangladesh banking sector - Newaz, M. K.; Ali, T.; Akhter, I. (BRAC University, 2010)
The employment culture is changing in Bangladesh. It is now relatively common to change jobs frequently, rather than to grow with one company throughout the employment life. This kind of voluntary turnover directly affects the performance of the organization. So now all organizations are highly concerned to keep their valuable employees. Each day completed by an employee is an investment to an organization; to leave before the full term is to get no return on the investment. As banking is one of the vital service industry for any country and performing a number of roles in the economy, so it has been chosen by the researchers for this study. Like all other industries, banking sector in our country is also facing the same employee turnover problem. It is needless to say, healthy banking system and healthy economies seem to go together. In order to ensure that, banking sectors should focus on the factors, which are primarily responsible for employees leaving the organization. This paper mainly tries to focus on different perceived reasons of employees of financial sector for leaving decision from their existing organizations